EFFECT OF E-PROCUREMENT, INTERNAL CONTROL EFFECTIVENESS, GOOD GOVERNANCE, ON FRAUD PREVENTION WITH ORGANIZATIONAL ETHICAL CULTURE AS MODERATING VARIABLE (STUDY ON LOCAL GOVERNMENT IN EAST JAVA PROVINCE) - Dina Ayu Putri; Sarwenda Biduri; Sigit Hermawan; Wiwit Hariyanto (International Journal of Economic Integration and Regional Competitiveness, 2024)
This study proves and analyzes the influence of each e-procurement, the effectivity of internal control, and good governance on fraud prevention with the organization's ethical culture as a moderation variable. This study used the ULP Working Group (Procurement Service Unit Working Group) in the Sidoarjo Regency Government, Pasuruan Regency, and Pasuruan City as its population, comprising 66 people. Samples were selected using the random sampling method. This study used a quantitative approach with research data collected using a Likert scale and tested using smartPLS partial last square program data processing. The calculation results show that e-procurement, effectivity internal control, and good governance directly influence fraud prevention. Other results also show that e-procurement, effectivity internal control, and good governance indirectly influence fraud prevention, which is influenced by another variable, namely the organization's ethical culture